Functional teleology and the coherence of Ephesians: a comparative and reception-historical approach - Covington, Eric (Wissenschaftliche Untersuchungen zum Neuen Testament, 2018)
Cover -- Preface -- Table of Contents -- List of Abbreviations -- Chapter 1: Introduction -- Chapter 2: The Question of Coherence in Ephesians -- 2.1. Introduction -- 2.2. The Conceptual Coherence of Ephesians in Recent Scholarship -- 2.2.1. Ephesians and Post-1940s Ecclesiology -- 2.2.2. Ephesians and Gnosticism -- 2.2.3. Ephesians in Modern Comparative Study -- 2.2.4. Ephesians and Greco-Roman Rhetoric -- 2.2.5. Ephesians and Ancient Political Philosophy -- 2.2.6. Ephesians and Ancient Folk Religion -- 2.2.7. Ephesians and Socio-Scientific Studies -- 2.2.8. Summary: The Problem of Conceptual Coherence in Ephesians -- 2.3. Observation: Modern Virtue Ethics and Ancient Ethical Thought -- 2.3.1. Telos and Human Function in Ancient Ethical Thought -- 2.3.2. The Erosion and Inversion of Teleological Thought in Modernity -- 2.4. Hypothesis, Aims, and Structure -- 2.4.1. Hypothesis: Ephesians and the Logic of Functional Teleology -- 2.4.2. Previous Teleological Approaches in New Testament Studies -- 2.4.3. Preliminary Definitions -- 2.4.4. Aims and Structure -- 2.5. Method and Methodology -- 2.5.1. Reading Ephesians within the Ancient Thought World -- 2.5.2. Analogical Comparative Studies in Biblical and Ancient Philosophical Ethics -- 2.5.3. Auslegungsgeschichte and the Interpretation of Ephesians -- Part One: Functional Teleology in the Ancient Thought World -- Chapter 3: Teleology in Ancient Ethical Thought -- 3.1. Introduction -- 3.2. The Tablet of Cebes and Ancient Teleological Ethics -- 3.2.1. The Tablet of Cebes -- 3.2.2. Teleological Ethics and The Tablet of Cebes -- 3.2.3. Teleology in Ancient Ethics -- 3.3. The Corporeal Metaphor, Teleology, and the Functional Argument -- 3.3.1. The Corporeal Metaphor and the Functional Argument in Aristotle -- 3.3.2. The Corporeal Metaphor and the Functional Argument in Other Ethical Traditions